AVALIAÇÃO DA COMPOSIÇÃO MINERAL DE PÃES ELABORADOS COM TRIGO, AVEIA E SOJA - Klajn, Vera M.; Fiorentini, Angela M.; Soares, José M.; Hermanns, Gislaine; Schöffer, Jéssie d. N.; Kinalski, Tenisa (Salão do Conhecimento, 2013)
Resumo